(untitled) (Agricultural Engineering, 2019)
Assessment of the colour with the use of many parameters is used with reference to evaluation of the quality changes of products resulting from application of specific technological treatments. The paper investigates the effect of relations between parameters of irradiation of potato bulbs with UVC on selected coefficients of assessment of the colour of fries determined with CIE L*a*b* method. It was statistically significantly proved that UV-C radiation affected brightness of fries, change in colour, recognition of the difference in colour and intensity of the colour reception. Statistical analysis of results was carried out at the assumed level of significance α=0.05.